Analysis of Racism in “12 Years A Slave” Movie Directed By Steve Mcqueen - Mohammad Fadil Pakaya; Ana Mariana; Dahlia Husain (Institut Agama Islam Negeri (IAIN) Manado, 2021)
AbstractAnalysis of Racism in “12 Years A Slave” Movie Directed By Steve Mcqueen. Racism mostly still happens in many countries, especially the country with a lot of majorities and minority groups with very strict differences in characteristics such as in the United States of America or other European countries. This action is depicted very clearly in racism in 12 years movie. The study aims to analyze racism in 12 years movie directed by Steve Mcqueen. The method used is descriptive qualitative. The result of the study shows that racial prejudice that occurs in 12 Years a Slave Movie happened in the four social aspects of social structure, there are in the aspect of economic life, political and legal process, and in educational aspect. This study also reveals that the novel also reflects the racial prejudice in its social aspects of social structure in Southern America in the 1950s.Keywords: racism, discrimination, characters